Платформний підхід до ідентифікації циклів взаємодії у полісубʼєктному середовищі лісоресурсної сфери - Сакаль, О.В.; Третяк, Н.А. (Економіка природокористування і сталий розвиток, 2019)
Досліджено сутнісні ознаки платформи системних взаємодій лісоресурсного та ринкового циклів розвитку. Для ідентифікації її структури і функцій запропоновано використовувати концепцію Міжурядової науково-політичної платформи з біорізноманіття та екосистемних послуг. Визначено зміст поняття лісоресурсного циклу розвитку. Обґрунтовано цілі, мету і функції платформи лісоресурсного та ринкового циклів розвитку на загальнодержавному рівні. The article is devoted to the study of the essential features of the systemic interaction platform of forest resource and market cycles of development. In order to identify the structure and functions of such a platform, it is proposed to use the concept of the Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services. The systemic characteristics of the formation of the interaction platform of forest resource and market cycles of development, and, accordingly, and the functions of such a platform, are determined by an integrated set of factors of both economic, social and environmental content. At the same time, environmental factors are the most important and the least manageable, since they are governed by the laws of the principle of limiting factors. We define the forest resource development cycle as the transformation of social relations in the use, protection and reproduction of forest resources in accordance with socio-economic conditions and forest resource restrictions, which are caused by the laws of the limiting factors principle, in a certain period of social development. The adapted conceptual structure of the platform of forest resource and market cycles of development encompasses six interrelated elements that make up the socio-ecological and economic system, which operate on different scales in time and space, which collectively represents the unity of forest resource and market cycles. Among the functions of the systemic interaction platform of forest resource and market cycles of development at the national level are the following: involvement of all stakeholders; coordination; providing tools and services; defining rules and standards. At the same time, the main function of the platform is to provide the prerequisites for the ecologically balanced production of economic benefits as a result and resources of forestry, logging and to some extent forest processing activities by directing the processes of subsystem management of such activities to create and further functioning sustainable economic systems (or their complexes) within the overall structural model system economy.